2021
DOI: 10.1186/s12966-021-01086-y
|View full text |Cite
|
Sign up to set email alerts
|

Food environment intervention improves food knowledge, wellbeing and dietary habits in primary school children: Project Daire, a randomised-controlled, factorial design cluster trial

Abstract: Background Evidence suggests that dietary intake of UK children is suboptimal. As schools provide an ideal natural environment for public health interventions, effective and sustainable methods of improving food knowledge and dietary habits in this population must be identified. Project Daire aimed to improve children’s health-related quality of life, wellbeing, food knowledge and dietary habits via two multi-component interventions. Methods Daire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 31 publications
(49 reference statements)
0
45
0
3
Order By: Relevance
“…Indeed, HAF leads explained that they delivered more than simply ‘nutritional’ education, and instead involved a range of food-related information, to improve families’ overall food literacy. This is promising as prior research has shown that school-based nutritional education interventions, which similarly demonstrate a whole-school approach are beneficial for improving a range of outcomes, including wellbeing, dietary intake, and cooking competence and confidence [ 18 ]. Moreover, the fact that providers considered food literacy to be additional to nutritional education suggests that some providers may have produced their own working definition of what they consider nutritional education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, HAF leads explained that they delivered more than simply ‘nutritional’ education, and instead involved a range of food-related information, to improve families’ overall food literacy. This is promising as prior research has shown that school-based nutritional education interventions, which similarly demonstrate a whole-school approach are beneficial for improving a range of outcomes, including wellbeing, dietary intake, and cooking competence and confidence [ 18 ]. Moreover, the fact that providers considered food literacy to be additional to nutritional education suggests that some providers may have produced their own working definition of what they consider nutritional education.…”
Section: Discussionmentioning
confidence: 99%
“…Other child-focused cooking programmes have similarly demonstrated benefits surrounding cooking competence and willingness to try new foods, which is assumed to relate to the repeated exposure to foods during the sessions and improved self-efficacy [ 16 ]. Likewise, food education is a compulsory element of the school curriculum in England, and research on school-based nutritional education has found a whole-school approach, involving a range of repeated social and practical food experiences such as group education on food provenance, cooking and tasting experiences, to be beneficial for cooking competence, wellbeing and dietary change [ 17 , 18 ]. Finally, the school-dining experience affords opportunities for social interactions with peers, which has shown to improve well-being and dietary habits, including trying of foods and dining etiquette, through social learning and modelling [ 19 ]; such environments may therefore play a vital role in increasing children’s food literacy and cooking confidence within the HAF programme.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to data analysis, where necessary, items were reversed coded so that a higher score indicated greater perceived cooking competence for all items. All analyses were conducted using IBM SPSS Statistics v25 and IBM SPSS Amos v25, with a significance level of 0.05. a larger study (Project Daire) [44]. For this sample, 50.32% were female.…”
Section: Piloting and Initial Face Validitymentioning
confidence: 95%
“…CooC7 (6-7 year olds) Participants and procedure Sample 4: Data from 514 primary school children aged 6-7 completed baseline measurements as part of a larger study (Project Daire) [44], are used as Sample 4. For this sample, 48.63% were female.…”
Section: Psychometric Testing Validation and Data Analysismentioning
confidence: 99%
“…Food Exposure and Willingness to try were adapted from Birch and Sullivan (1991) and Morgan et al (2010), previously used in a similar age group in Northern Ireland (Brennan et al, 2021). Children were presented with six images of vegetables and asked whether they had tasted the food before.…”
Section: Food Exposure and Willingness To Trymentioning
confidence: 99%